Models of sarcopenia: Short review. (1st July 2017) - Palus, S.; Springer, J.I.; Doehner, W.; von Haehling, S.; Anker, M.; Anker, S.D.; Springer, J.
Abstract: Approximately 40–50% of the population over 80 years of age suffers from sarcopenia making this condition a major geriatric clinical disorder and a key challenge to healthy aging. The hallmark symptom of sarcopenia is the loss of muscle mass and strength without the loss of overall body weight. Sarcopenic patients are likely to have worse clinical outcomes and higher mortality compared to healthy individuals. This review will focus on animal models designed to study sarcopenia including hind-limb unloading, de-nervation, and immobilization by using casts or wire strategies, as well as using aged rodents. Currently there are no registered treatments for sarcopenia. Most sarcopenic individuals show signs of physical frailty, which leads to increases the prevalence of balance disorders, falls, fractures and pain. Therefore, is it essential to develop and use relevant animal models to further the research on sarcopenia therapy? Highlights: Covers all animal models of sarcopenia Explains the usefulness of individual models Suggests corresponding human pathology to the models